Vemurafenib (RG67204, PLX4032): a potent, selective BRAF kinase inhibitor. (May 2012) - Patrawala, Samit; Puzanov, Igor
Vemurafenib is a potent inhibitor of the mutated BRAF kinase. Phase I and II clinical trials of vemurafenib showed response rates of more than 50% in patients with metastatic melanoma and BRAF mutation. A Phase III study comparing vemurafenib with dacarbazine in 675 previously untreated patients revealed overall survival to be 84% (95% CI: 78–89) in the vemurafenib group and 64% (95% CI: 56–73) in the dacarbazine group. Vemurafenib was associated with a relative reduction of 63% in the risk of death and 74% in the risk of either death or disease progression, as compared with dacarbazine (p < 0.001). Progression-free survival was longer in those treated with vemurafenib (median: 5.3 vs 1.6 months; hazard ratio: 0.26; 95% CI: 0.20–0.33). Response rates were 48% for vemurafenib and 5% for dacarbazine. After review of the interim analysis by an independent data and safety monitoring board, crossover from dacarbazine to vemurafenib was recommended.